Business Statistics: for Non-Mathematicians - Sonia Taylor (Great Britain Bloomsbury Academic, 2022)
Business Statistics is a student-friendly book written to encourage first year business students to understand their first experience of statistics. Each topic is well illustrated, with worked examples, tutorial sheets, supplementary exercises, and computer worksheets in SPSS, Minitab and Excel - all with answers provided. An extensive Companion Website complements the book with additional learning tools. Examples are plentiful, and are based on real world scenarios to create a relevant, problem-based approach covering the practical and theoretical.
Keywords: Business; Statistics; Mathematics; Textbooks; Research Methods (BIN2044-N)